1992
DOI: 10.1002/bit.260390106
|View full text |Cite
|
Sign up to set email alerts
|

Electrically promoted protein production by mammalian cells cultured on the electrode surface

Abstract: Protein production of mammalian cells has been promoted by applying a small constant potential to the surface of an electrode on which cells are cultured. Human carcinoma line of MKN45 cells were cultured on the surface of a platinum-coated plastic plate electrode. Low d.c. voltage of constant potential was applied to the electrode during 4-day culture to modulate the production of carcinoembryonic antigen (CEA). The amounts of both secreted and membrane-bound CEA were dependent on the applied potential during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Electrical stimulation has shown its capacity to modulate cell membrane permeability [35] and cytoskeletal structure [36]. Furthermore, reduced cell membrane fluidity was reported during ES [36].…”
Section: Discussionmentioning
confidence: 98%
“…Electrical stimulation has shown its capacity to modulate cell membrane permeability [35] and cytoskeletal structure [36]. Furthermore, reduced cell membrane fluidity was reported during ES [36].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism by which ES regulates Schwann cell functions is unclear. ES is capable of modulating cell membrane permeability,33 membrane fluidity, and cytoskeletal structure 34. All of these ES‐mediated effects are related to cell membrane structure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies pointed out that the electro-stimulation could affect microbial growth and activity, and proper electro-stimulation could promote microbial metabolism (Thrash and Coates, 2008). Kojima et al (1992) used 0.2-0.6 V potential to stimulate MKN45 cells (Carcinoma cells) in a culture dish with Pt as the anode and cathode, and showed that current stimulation could change the DNA, protein synthesis, membrane permeability and cell growth. Furthermore, heterotrophic bacterial viability was also observed to be not significantly affected when the applied electric current density was less than 6.2 A/m 2 , but was partly inactivated at current densities more than 12.3 A/m 2 in a membrane reactor (Wei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%